Surgical organ displacement: what is the best “materials and methods” for proton radiotherapy? - Ogino, Takashi (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
In the mid 1940s, Robert Wilson (1) hypothesized that a highly localized deposition of energy from a proton beam could be used to increase the radiation dose to tumors while minimizing radiation to adjacent normal tissues. The depth-dose distribution of a proton beam differs significantly from that of a photon beam. Protons show increasing energy deposition with penetration distance, reaching a maximum-named the Bragg peak-near the end of the range of the proton beam. In front of the Bragg peak, the dose level is modest compared to photon beams; beyond the Bragg peak, the dose decreases to nearly zero. By choosing the appropriate proton beam energy, the depth of the Bragg peak can be adjusted to match the depth and extent of the target volume. Therefore, excellent conformality can be achieved, in contrast to conventional or intensity-modulated radiotherapy (IMRT).